Being European: "Hamlet" on the Israeli Stage - Barzilai, Reut (Multicultural Shakespeare: Translation, Appropriation and Performance, 2020)
One of the most prolific fields of Shakespeare studies in the past two decades has been the exploration of local appropriations of Shakespeare’s plays around the world. This article, however, foregrounds a peculiar case of an avoidance of local appropriation. For almost 60 years, repertory Israeli theaters mostly refused to let Hamlet reflect the “age and body of the time”. They repeatedly invited Europeans to direct Hamlet in Israel and offered local audiences locally-irrelevant productions of the play. They did so even though local productions of canonical plays in Israel tend to be more financially successful than those directed by non-Israelis, and even when local national and political circumstances bore a striking resemblance to the plot of the play. Conversely, when one Israeli production of Hamlet (originating in an experimental theatre) did try to hold a mirror up to Israeli society—and was indeed understood abroad as doing so—Israeli audiences and theatre critics failed to recognize their reflection in this mirror. The article explores the various functions that Hamlet has served for the Israeli theatre: a rite of passage, an educational tool, an indication of belonging to the European cultural tradition, a means of boosting the prestige of Israeli theatres, and—only finally—a mirror reflecting Israel’s “age and body.” The article also shows how, precisely because Hamlet was not allowed to reflect local concerns, the play mirrors instead the evolution of the Israeli theatre, its conflicted relation to the Western theatrical tradition, and its growing self-confidence.